How to Implement Employee Assistance Programs in Higher Education: A Literature Review - Nurhadi, Didik (Fakultas Teknik Universitas Negeri Malang, 2020)
Higher education leaders need to establish Employee Assistance Programs (EAPs) by understanding the challenges faced by the higher education based on strategies to effectively meet the needs to achieve better employees' performance in their field. The EAPs in higher education focuses on the unique challenges of employee assistance service delivery in a university setting. This paper discussed the preparation, implementation, and evaluation of the EAPs in higher education through a framework of the EAPs application in a higher education institution. This insight was expected to provide insight to university leaders who wished to effectively implement the EAPs in their higher education in the face of changing labour demand and competition challenges in the labour market.